Energy, Environment and Sustainable Development - Uqaili, Mohammad Aslam; Harijan, Khanji (Springer Vienna : Imprint: Springer, 2012)
New information and strategies for managing the energy crisis from the perspective of growing economies are presented. Numerous case studies illustrate the particular challenges that developing countries, many of which are faced with insufficient resources, encounter. As a result, many unique strategies to the problems of energy management an conservation, environmental engineering, clean technologies, biological and chemical waste treatment and waste management have been developed.